Nucleic acid-lipid membrane interactions studied by DSC - Sarantis Giatrellis; George Nounesis (Wolters Kluwer Medknow Publications, 2011)
The interactions of nucleic acids with lipid membranes are of great importance for biological mechanisms as well as for biotechnological applications in gene delivery and drug carriers. The optimization of liposomal vectors for clinical use is absolutely dependent upon the formation mechanisms, the morphology, and the molecular organization of the lipoplexes, that is, the complexes of lipid membranes with DNA. Differential scanning calorimetry (DSC) has emerged as an efficient and relatively easy-to-operate experimental technique that can straightforwardly provide data related to the thermodynamics and the kinetics of the DNA-lipid complexation and especially to the lipid organization and phase transitions within the membrane. In this review, we summarize DSC studies considering nucleic acid-membrane systems, accentuating DSC capabilities, and data analysis. Published work involving cationic, anionic, and zwitterionic lipids as well as lipid mixtures interacting with RNA and DNA of different sizes and conformations are included. It is shown that despite limitations, issues such as DNA- or RNA-induced phase separation and microdomain lipid segregation, liposomal aggregation and fusion, alterations of the lipid long-range molecular order, as well as membrane-induced structural changes of the nucleic acids can be efficiently treated by systematic high-sensitivity DSC studies.